Different responses to steady and fluctuating UV-B radiation treatments between two grapevine cultivars, and the underlying photoreceptor mechanisms involved in Arabidopsis - Su-Zhou, Chenxing; Durand, Maxime; Martinez-Abaigar, Javier; Shapiguzov, Alexey; Kangasjärvi, Saijaliisa; Liu, Xu; Robson, Matthew T. (Elsevier, 2026)
Ultraviolet–B radiation (UV-B) is the most-energetic region of the solar spectrum received by plants and its absorption by leaves requires specialised adaptations. Natural light is essentially dynamic, yet the effects of fluctuating UV-B radiation on plant ecophysiology remain poorly understood. We investigated how two grapevine (Vitis vinifera) cultivars, Tempranillo (red) and Viura (white), respond to fluctuating and steady UV-B treatments in a controlled environment, and explored the underlying processes mediating acclimation using photoreceptor mutants of Arabidopsis thaliana. Plants were grown in a greenhouse under the same daily dose of fluctuating or steady UV-B radiation, paired with their respective attenuated UV-B controls. Leaf chlorophyll epidermal flavonols and photosynthetic capacity were monitored in both cultivars as well as photoassimilates in Arabidopsis. Acclimation was cultivar-specific: whereby flavonol accumulation in response to UV-B was greater in Viura (a 28 % increase), although in Tempranillo within-treatment flavonol accumulation was associated with less inhibition of operating efficiency of photosystem II (ɸPSII). In Arabidopsis, responses to both fluctuating and steady UV-B regimes were primarily mediated by the photoreceptor UV RESISTANCE LOCUS 8, with cryptochromes also contributing to flavonol regulation and playing a greater role in photoassimilate accumulation under steady UV-B. Knowledge of these processes across cultivars and conditions can assist in grapevine selection, to guide photoreceptor-centric approaches on the basis of differences in UV-B-radiation acclimation capacity, and to support vineyard management under naturally variable UV-B conditions. These aspects are increasingly important under current global climate change scenarios for such a widespread crop as grapevine.
Keywords: ultraviolet radiation; photoreceptor; flavonol; photosystem II; starch; acclimation; grapevine